2019
DOI: 10.1021/acs.iecr.9b01273
|View full text |Cite
|
Sign up to set email alerts
|

Novel Cu-Based CHA/AFI Hybrid Crystal Structure Catalysts Synthesized for NH3-SCR

Abstract: Cu/SAPO-34/5 catalysts were prepared by a traditional hydrothermal/impregnation method to investigate the effect of SAPO-34/5 on deNO x performance over Cu/SAPO-34/5 (the proportion of SAPO-34/SAPO-5 calculated by its main diffraction peak intensity). These characteristic results prove the fact that the superior deNO x performance of Cu/SAPO-34/5(3.16) is due to its most abundant Brønsted (B) acid sites and active isolated Cu 2+ . A higher amount of B acid sites over ) is better to disperse and stabilize the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…For the CuTiO x catalyst, two types of isolated Cu 2+ ions characterized by the four hyperfine splitting lines overlap the broad signal with two different values for parallel components of g // (H 1 ) = 2.43 and g // (H 2 ) = 2.33, which have A // (H 1 ) = 78 G and A // (H 2 ) = 192 G, respectively. The value for the g-tensor is the fingerprint of the Cu 2+ ions located at an axially distorted octahedron, indicating the existence of Cu 2+ occupying the Ti 4+ sites in the TiO 2 lattice . The component having two different resonance parameters, g // (H 1 ) = 2.43 and g // (H 2 ) = 2.33, with a perpendicular parameter, g ⊥ = 2.06, can be assigned to Cu 2+ ions at substitutional cation sites of TiO 2 with different coordination numbers. , Similar signals corresponding to the formation of Cu 2+ ions in substituted octahedral sites with a tetragonal distortion have also been observed upon Cu 2+ incorporated ZrO 2 and TiO 2 surfaces. , The spectra feature of the CuO/TiO 2 catalyst evidence the only existing form of the CuO nanoparticle since no other isolated Cu 2+ ion induced anisotropic hyperfine structures were detected.…”
Section: Resultsmentioning
confidence: 98%
“…For the CuTiO x catalyst, two types of isolated Cu 2+ ions characterized by the four hyperfine splitting lines overlap the broad signal with two different values for parallel components of g // (H 1 ) = 2.43 and g // (H 2 ) = 2.33, which have A // (H 1 ) = 78 G and A // (H 2 ) = 192 G, respectively. The value for the g-tensor is the fingerprint of the Cu 2+ ions located at an axially distorted octahedron, indicating the existence of Cu 2+ occupying the Ti 4+ sites in the TiO 2 lattice . The component having two different resonance parameters, g // (H 1 ) = 2.43 and g // (H 2 ) = 2.33, with a perpendicular parameter, g ⊥ = 2.06, can be assigned to Cu 2+ ions at substitutional cation sites of TiO 2 with different coordination numbers. , Similar signals corresponding to the formation of Cu 2+ ions in substituted octahedral sites with a tetragonal distortion have also been observed upon Cu 2+ incorporated ZrO 2 and TiO 2 surfaces. , The spectra feature of the CuO/TiO 2 catalyst evidence the only existing form of the CuO nanoparticle since no other isolated Cu 2+ ion induced anisotropic hyperfine structures were detected.…”
Section: Resultsmentioning
confidence: 98%
“…This can be confirmed by the 29 Si MAS NMR and 27 Al MAS NMR. The 29 Si MAS NMR spectra of Fr–Zn­( y )/Z5 catalysts showed one intense and two weak resonance peaks at around −113.3, −106.8, and −103.0 ppm (Figure A–C), attributing it to the Q 4 Si­(4Si,0Al), Q 3 Si­(3Si, 1Al), and Q 2 Si­(2Si, 2Al), respectively. When the catalyst was deactivated, the peak intensity of Q 4 Si markedly decreased, along with the appearance of a new peak at −118.2 ppm. Some previous investigations indicated that the generated coke species could distort the Si–O–Si bond of zeolite framework, resulting in the broadening and migration of chemical shift in the 29 Si NMR spectra. , This deformation of the crystal structure was also observed by XRD patterns (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Cu-zeolites with a combination of two zeolite structures showed enhanced HTA stability over single catalyst. For example, Cu-ZST-1 (AFX/CHA), 15 Cu-SAPO-34/5 (CHA/AFI), 16 and Cu-OFF/CHA 17 composites exhibited improved hydrothermal stability than the individual component. Our previous work also showed that the mixed Cu-SSZ-13/Cu-SAPO-34 composites performed a much better HTA stability than Cu-SSZ-13, due to the intense interaction between the two components (SSZ-13 and SAPO-34) during HTA.…”
Section: Introductionmentioning
confidence: 99%